AUTHENTIC MATERIALS FOR TEACHING WRITING: A CRITICAL LOOK - Rashidova G. I. (Journals Park Publishing, 2024)
Teaching writing is hard work. Selecting materials that are suitable for their pupils can be a challenge for writing instructors. The following subjects will be explained in this article: 1) Previous research on the topic; 2) the types of authentic materials that can be used to teach writing; 3) the advantages and disadvantages of doing so; and 4) the theoretical relationship between content-based instruction and authentic materials that language teachers can use to teach writing in the classroom. A qualitative research methodology was utilized, concentrating on content analysis. Documentation and human instruments were the main tools used.
Keywords: authentic material, challenge, content-based, instruction, writing.